The Influence of “Every U Does Good Heroes” Public Relations Campaign Message on Followers Attitudes regarding Unilever Indonesia’s Vision and Mission on Instagram @unileveridn - Vienny Chikita; Fanny Lesmana; Inri Inggrit Indrayani (Petra Christian University, 2024)
This research was intended to explain the influence of campaign message Every U Does GoodHeroes on the followers of @unileveridn. Unilever Indonesia has run a campaign of Every U DoesGood Heroes since August 2021 until now. The campaign invites individuals or companies toextend kindness to others in simple ways. To provide kindness for around, Indonesia Unileverguides on three pillars that are in line with this campaign. These pillars are building moresustainable planets, improving the health and well-being of the community, and contributing to ajust and inclusive society. The kind of research is explanatory quantitative, with online methodsof surveys and simple linear regression as data analysis techniques. The number of samples, asmany as 100 followers of @unileveridn based on purposive sampling. Research has shown thatcampaign messages influence the followers of @unilever. The highest influence is on the messagestructure sub-indicator, namely conclusion statement. The lowest influence is in the message'scontent sub-indicator, supporting material that contains the purpose of campaign message.Research shows that variable x: public relations campaign message also has strong correlation withvariable y: attitude. This was due to campaign messages consistent with three pillars of UnileverIndonesia.